AN INTEGRATED APPROACH TO DETERMINATION AND EVALUATION OF PRODUCTION PLANNING PERFORMANCE CRITERIA - Guengoer, Ceyda; Cenkci, Doruk (YILDIZ TECHNICAL UNIV, 2009)
Production planning is used to control and systematically monitor the inputs and outputs of the production activities changing according to structure of organizations. The aim of this study is to present an integrated approach for performance measurement of the production planning process that plays a key role in organizations' success. In the first phase of the presented approach, the nominal group technique, a group decision making technique, is proposed to use for determining the appropriate production planning performance criteria. In the second phase, these performance criteria are evaluated in respect of organizations' priorities through a fuzzy analytic hierarchy process (AHP), a multi-criteria decision making method. In the final phase, a general production planning performance measure is obtained by using pre-weighted performance criteria and several metrics for these criteria. The application of the proposed approach is demonstrated in a multinational tire company.
Keywords: Production planning; performance criteria; nominal group technique; fuzzy AHP; ANALYTIC HIERARCHY PROCESS; SELECTION; Engineering